2008
DOI: 10.4161/cc.7.4.5355
|View full text |Cite
|
Sign up to set email alerts
|

REGγ proteasome activator is involved in the maintenance of chromosomal stability

Abstract: REGγ is a member of the 11S regulatory particle that activates the 20S proteasome. Studies in REGγ deficient mice indicated an additional role for this protein in cell cycle regulation and proliferation control. In this paper we demonstrate that REGγ protein is equally expressed throughout the cell cycle, but undergoes a distinctive subcellular localization at mitosis. Thus, while in interphase cells REGγ is nuclear, in telophase cells it localizes on chromosomes, suggesting a role in mitotic progression. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 27 publications
6
46
0
Order By: Relevance
“…It is worth noting that PA28 γ is localized in the nucleus in interphase cells and on chromosomes in telophase cells, suggesting a role in mitotic progression. This conclusion is supported by the marked aneuploidy (chromosomal gain and loss), supernumerary centrosomes, and multipolar spindles observed in the fi broblasts of PA28 γ -defi cient mice (Zannini et al , 2008 ). These fi ndings underscore a previously uncharacterized function of PA28 γ in centrosomes and chromosomal stability.…”
Section: Role Of Pa28 and Pa200supporting
confidence: 71%
“…It is worth noting that PA28 γ is localized in the nucleus in interphase cells and on chromosomes in telophase cells, suggesting a role in mitotic progression. This conclusion is supported by the marked aneuploidy (chromosomal gain and loss), supernumerary centrosomes, and multipolar spindles observed in the fi broblasts of PA28 γ -defi cient mice (Zannini et al , 2008 ). These fi ndings underscore a previously uncharacterized function of PA28 γ in centrosomes and chromosomal stability.…”
Section: Role Of Pa28 and Pa200supporting
confidence: 71%
“…This REGg redistribution and interaction with MEKK3 may be significant in the context of mitosis progression and exit [38]. Interestingly, it was reported that REGg undergoes an intranuclear redistribution at mitosis [43]. During telophase, REGg was found to be localized on the chromosomes [43].…”
Section: Regulation Of Reggmentioning
confidence: 95%
“…Decreased levels of p53 allow cells to pass through the G1/S checkpoint during cell cycle progression. Other studies have shown that REGg may play a key role in chromosomal stability during mitosis [43] and in the organization of nuclear speckles [44]. Furthermore, there was a report implicating a potential function of REGg in regulating the activity of G protein-coupled receptors through binding with the C-terminus of thromboxane A 2 receptor [45].…”
Section: Biological Functions Of Reggmentioning
confidence: 97%
See 1 more Smart Citation
“…Although sumoylation has most often been implicated in promoting nuclear import (11), there is evidence that sumoylation can also serve as a signal for cytoplasmic translocation of some protein substrates, such as TEL (39), Smad3 (13), Med (23), MEK1 (34), and heterogeneous nuclear ribonucleoproteins M and C (37). REG␥ has been suggested to be a potential nucleocytoplasmic shuttling protein (42). However, the mechanisms regulating REG␥ nuclear import/export have not yet been fully characterized.…”
Section: Discussionmentioning
confidence: 99%